The complete chloroplast genome sequence of Rhodiola sacra (Prain ex Hamet) S. H. Fu. Issue 2 (3rd July 2019) - Zhao, Kaihui; Xu, Yuanjiang; Peng, Shiyuan; Li, Lianqiang; Quan, Hong; Liao, Zhihua; Lan, Xiaozhong
Abstract: Rhodiola sacra (Prain ex Hamet) S. H. Fu is a traditional natural plant pharmaceutical with anti-hypoxia effect and mainly distributed in Yunnan and Tibet (China). The complete chloroplast sequence of R. sacra was determined in our study. The cpDNA was 150, 941 bp in length, containing a pair of inverted repeats (IRs) of 25, 873 bp each separated by a large and small single copy (LSC and SSC) regions of 82, 161 bp and 17, 034 bp, respectively. The genome contained 84 protein coding genes, eight rRNA genes and 36 tRNA genes. Phylogenetic tree revealed that R. sacra closely related to Rhodiola kirilowii and Rhodiola crenulata .